An Infrared-Aided Lighting Control System For Physically Impaired - Omotosho Oludayo Hannah; Michael O. Kolawole (Institute of Advanced Engineering and Science, 2013)
In recent years the need to provide greater convenience for the physically impaired community is a challenging issue: the reason being that more reliable and cost effective system are required. This paper proposes a cost effective infrared-based solution for automatic control of electrical circuitry and systems in a residential building to aid easy access for physically impaired and/or elderly people. This electronic system has been designed to meet the need of users such that it switches ON the lighting circuits on the detection of entry into a room and switches OFF the circuit as soon as the room is empty. One of the most important features of this design is the ability to automatically adjust the power consumption on the basis of human presence in a room. The device is simple both in its functionality and implementation.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3627